In vitro study of the relation between the apical foramen and anatomical apex - Olivera-Rojas, Piero (2017)
Objective: To evaluate the relationship between the position of the apical foramen and the anatomic apex in uniradicular teeth. Materials and method: In this vitro study that included 71 teeth between incisors, canines and premolars, all of them were uniradicular. The position of the apical foramen (vestibular, palatal / lingual, mesial and distal) was evaluated as well as the distance from the apical foramen to the apex of the anatomic apex through an electronic Vernier. Results: In thirty-two dental pieces (45.1%) coincided the location between the apical foramen and anatomical apex; in 40 (56.4% ) the apical foramen was found at vestibular and palatal / lingual levels, In teeth where there was concordance, the largest amount was found at the level of the upper central incisors (31.3%). The distance between the position of the apical foramen and the anatomical apex was 0.36±0.41 mm. Conclusions: The apical foramen is more frequent at the vestibular and palatine / lingual levels. The coincidence between the position of the apical foramen and the apex of the anatomical apex is present in 45% of cases. The average distance between both anatomical structures was 0.36±0.41 mm; this distance being greater at the upper premolar.